Comparison of behaviors displayed by mothers of clinical and non-clinical preschoolers in a playing situation (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
To analyze interaction patterns that mothers have with their children with no behavioral problems might allow the evaluation of parent skills training programs, If the taught skills are the same that non-clinical children parents use in their daily life management. The objective of this study was to verify the existence of differences in the response of mothers with clinical and non-clinical preschool children in a playing semi-structured interaction. Frequency of emission of generic and descriptive praise, criticism and orders by the mother, and obedience, and non compliance by the child were measured and compared. The mothers on non-clinical children made less use of criticism behavior when compared with mothers of the clinical children. Praise and orders did not differ in the two groups. Children differ only in the non-compliance behavior. To teach mothers of clinical children to not punish inappropriate behaviors, may be as important to the clinical improvement than to teach them to praise appropriate behaviors.
Keywords: Mother child relations; problem child